PEMBERDAYAAN PARTISIPATIF DALAM MEMBANGUN KEMANDIRIAN EKONOMI DAN PERILAKU WARGA MASYARAKAT (Studi Pada Bank Sampah Wargi Manglayang RT 01 RW 06 Kelurahan Palasari Kecamatan Cibiru Bandung) - SHOMEDRAN SHOMEDRAN (Departemen Pendidikan Luar Sekolah FIP, 2016)
Implementation of participatory empowerment in the Bank's Trash Wargi Manglayang interesting to study because the condition is something that is relatively new on the empowerment skill of rubbish, empowerment activities that survive, understanding and skills of people who are still lacking, the utilization of natural resources, and still needs to be studied and given input in accordance with the main task and has not done much study on the participatory empowerment Waste Bank. The aim of research is to know about the implementation, achievement of results in building economic independence and behavior of citizens and mentoring. This study is based on the concepts and theories that the concept of community empowerment, independence, empowerment in terms of PNF, participatory, and the concept of Trash Bank. This study used a qualitative approach using qualitative descriptive method of the case. Data collection techniques used are observation, interview, and documentation study. The subjects included nine people consisting of the Bank's management Garbage, citizens and local authorities, as well as triangulation were performed on Waste Bank expert teams. Results of the study, among others; 1) the implementation of which has been running well characterized by the participation of community members in planning activities, socialization and meetings, implementation, extension and training, as well as participation in activities Waste Bank; 2) achievement of the results indicate the occurrence of a change of economic independence of citizens can be seen from the increase in revenue from savings garbage and the garbage processing business of craft; 3) the change in behavior of residents can be seen from the activities of people who are no longer dispose of waste, protecting the environment, depositing garbage and participation in social activities and Development; and 4) facilitation undertaken manager has done characterized by facilitation, strengthening, protection and support. From the results of research on participatory empowerment in building economic independence and the behavior of residents can be concluded already well under way which can be demonstrated by the participation of citizens, economic change characterized by an increase in revenue and have a business, the change of behavior of citizens towards the trash and has done mentoring by managers.